A mimicry of melioidosis by Klebsiella ozaenae infection - Ng, Teck Han; How, Soon Hin; Kuan, Yeh Chunn; Salam, Adzura; Abd. Aziz, Azian; Abdul Rani, Mohammed Fauzi (College of Pathologists, Academy of Medicine Malaysia, 2009)
Klebsiella ozaenae is a Gram negative bacillus. It has been described as a colonizer of oral and nasopharyngeal mucosa and is a cause of atrophic rhinitis. Klebsiella ozaenae has seldom been isolated from serious infections. However, several reports have stated that Klebsiella ozaenae may cause invasive infections and even mortality. We report a 55-year-old man with Klebsiella ozaenae infection causing abscesses involving the right eye and left kidney and possibly also in the brain, lungs and prostate. The isolates were sensitive to ceftazidime, ciprofloxacin, chloramphenicol, gentamicin and sulfamethoxazole-trimethoprim but resistant to ampicillin. He responded well to 4 weeks of i.v. ceftazidime and i.v. amoxycillin-clavulanic acid. To our knowledge, such a multiorgan infection has not been reported previously for this organism.